2018
DOI: 10.1016/j.ydbio.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The left-right asymmetry of liver lobation is generated by Pitx2c-mediated asymmetries in the hepatic diverticulum

Abstract: Internal organs exhibit left-right asymmetric sizes, shapes and anatomical positions, but how these different lateralities develop is poorly understood. Here we use the experimentally tractable Xenopus model to uncover the morphogenetic events that drive the left-right asymmetrical lobation of the liver. On the right side of the early hepatic diverticulum, endoderm cells become columnar and apically constricted, forming an expanded epithelial surface and, ultimately, an enlarged right liver lobe. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Consistent with this idea, a recent study in Xenopus showed that, as the early liver diverticulum buds off from the gut tube, hepatic endoderm cells on the right side become more apically constricted, with a greater length-to-width ratio, whereas left-sided cells appear rounder and more compact, indicating that distinct left-and right-sided morphogenetic programs are distinguished very early in liver morphogenesis (Fig. 4A; Womble et al, 2018). In this study, asymmetric expression of pitx2c in the mesoderm surrounding the left side of the early hepatic diverticulum (Fig.…”
Section: Liversupporting
confidence: 58%
See 2 more Smart Citations
“…Consistent with this idea, a recent study in Xenopus showed that, as the early liver diverticulum buds off from the gut tube, hepatic endoderm cells on the right side become more apically constricted, with a greater length-to-width ratio, whereas left-sided cells appear rounder and more compact, indicating that distinct left-and right-sided morphogenetic programs are distinguished very early in liver morphogenesis (Fig. 4A; Womble et al, 2018). In this study, asymmetric expression of pitx2c in the mesoderm surrounding the left side of the early hepatic diverticulum (Fig.…”
Section: Liversupporting
confidence: 58%
“…Furthermore, while the endoderm exhibits cellular-level asymmetries in the developing stomach and liver, no such lateralities have been identified in this tissue layer in the early midgut (Davis et al, 2008). The underlying cellular mechanisms at play in each tissue also vary widely, from LR differences in proliferation to asymmetries in cell shape, polarity, rearrangement and/or ECM remodeling (Davis et al, 2008(Davis et al, , 2017Hecksher-Sørensen et al, 2004;Kurpios et al, 2008;Sivakumar et al, 2018;Welsh et al, 2013;Womble et al, 2018;Fig. 4).…”
Section: Similarities and Differences Between Asymmetric Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…During formation of the liver in Xenopus embryos, endoderm cells on the right side become columnar and apically constricted, whereas those on the left side become rounder and rearrange into a compact structure. 119) The development of such cellular asymmetries is regulated by Pitx2c and is responsible for the generation of future morphological asymmetries of the adult liver. Of interest, the cellular response to Pitx2c in the developing liver is opposite to that apparent in the embryonic midgut, in which endoderm cells on the left side of the dorsal mesentery 158) remain columnar and those on the right side become compact.…”
Section: Transcriptional Regulation Of Nodal Andmentioning
confidence: 99%
“…The liver and diaphragm are closely adjacent to each other and the movement of one is reflected in the movement of the other ( 53 ). In dogs, the greatest proportion of the liver lies to the right of the median plane, with a right-to-left proportion of liver of approximately 3:2 ( 55 ) whereas the ratio in humans ranges from 5:1 to 6:1 ( 56 ). Although the detection of DE at the right hemidiaphragm in humans is easier due to a larger window of the liver relative to the splenic window on the left side ( 15 ), DE detection on the left hemidiaphragm could be interrupted by gas in the GI, especially in the stomach.…”
Section: Discussionmentioning
confidence: 99%